Doppler ultrasound and D-dimer - Riopel, C.; Bounameaux, H. (Hämostaseologie, 2012)
The diagnosis of venous thromboembolism has evolved considerably with the development of standardized diagnostic algorithms that include clinical probability assessment, D-dimer measurement and the use of non-invasive imaging modalities such as compression ultrasonography and computed tomography angiography. The implementation of these strategies aims to improve resource allocation and patient outcome. The judicious use of these diagnostic tools requires a thorough knowledge of the appropriate clinical setting in which every test and strategy is efficient and can be used safely. For this purpose, D-dimer measurement and compression ultrasonography are complementary: the former is mainly used to exclude VTE in selected patients, while the latter is used to confirm the presence of an underlying DVT.This review provides an appraisal of the features and use of D-dimer and compression ultrasonography in the context of suspected venous thromboembolism.
Keywords: D-dimer; ultrasonography; clinical probability; deep vein thrombosis